Unveiling the potential of mitochondrial dynamics as a therapeutic strategy for acute kidney injury - Hao, Yajie; Zhao, Limei; Zhao, Jing Yu; Han, Xiutao; Zhou, Xiaoshuang (Frontiers in Cell and Developmental Biology, 2023)
Acute Kidney Injury (AKI), a critical clinical syndrome, has been strongly linked to mitochondrial malfunction. Mitochondria, vital cellular organelles, play a key role in regulating cellular energy metabolism and ensuring cell survival. Impaired mitochondrial function in AKI leads to decreased energy generation, elevated oxidative stress, and the initiation of inflammatory cascades, resulting in renal tissue damage and functional impairment. Therefore, mitochondria have gained significant research attention as a potential therapeutic target for AKI. Mitochondrial dynamics, which encompass the adaptive shifts of mitochondria within cellular environments, exert significant influence on mitochondrial function. Modulating these dynamics, such as promoting mitochondrial fusion and inhibiting mitochondrial division, offers opportunities to mitigate renal injury in AKI. Consequently, elucidating the mechanisms underlying mitochondrial dynamics has gained considerable importance, providing valuable insights into mitochondrial regulation and facilitating the development of innovative therapeutic approaches for AKI. This comprehensive review aims to highlight the latest advancements in mitochondrial dynamics research, provide an exhaustive analysis of existing studies investigating the relationship between mitochondrial dynamics and acute injury, and shed light on their implications for acute renal failure. The ultimate goal is to advance the development of more effective therapeutic interventions for managing acute kidney injury.